VALIDITY OF SCIENCE BOOK ORIENTED SETS IN ENVIRONMENTAL POLLUTION MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Karennina Putri Aristyani; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aimed to describe the validity of SETS-oriented science book for junior high school students in environmental pollutions materials. In this research, researcher uses a quantitative descriptive method and uses validation sheet in the form of questionnaire as data-collection techniques. The questionnaire contains the criteria of material feasibility, language, and presentation. The result of validation gave the material feasibility score 3.9, for the language is 3.6, and the presentation criteria scored 3.9. So, it can be concluded that a science book with SETS-oriented is very well to be used as a learning facility according to the assessment of the validator.